Housing choice structure: examples of two different-size cities from Turkey - Alkay, Elif (International Journal of Strategic Property Management, 2015)
The distribution pattern of housing in any urban area will be extremely diverse and heterogeneous. The shape of this pattern depends on intrinsic properties of the housing units themselves as well as on accessibility, environmental quality and the capacity and quality of previously constructed housing stock. How do households make their choices and distribute themselves among such diverse housing areas? The aim of this investigation is to put the factors that could define the choice structure of households by focusing on two different-size cities in Turkey: the Istanbul Metropolitan Area (IMA), where the housing choice is expected to dependent upon economic behavior of households, and Bandırma (BND), a medium-size city, where the housing market is relatively weaker and the choice structure is expected to dependent upon the limited opportunities of supply. The investigation results show that households’ socio-economic characteristics dominate the choice structure in the IMA parallel to the expectation. Housing properties have a more notable impact on the choice structure in BND that acknowledged the relative limitation of the housing market.First Publish Online: 19 Jun 2015